2005
DOI: 10.1016/j.acra.2004.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of combining MR perfusion, angiography, and 3He ventilation imaging for evaluation of lung function in a porcine model1

Abstract: Rationale and Objective-To assess the feasibility of combining magnetic resonance (MR) perfusion, angiography, and 3 He ventilation imaging for the evaluation of lung function in a porcine model. Materials and Methods-Fourteen consecutive porcine models with externally delivered pulmonary emboli and/or airway occlusions were examined with MR perfusion, angiography, and 3 He ventilation imaging. Ultrafast gradient-echo sequences were used for 3D perfusion and angiographic imaging, in conjunction with the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…Image registration of hyperpolarized gas MRI has previously been published in the context of perfusion MRI using controlled gas administration in pigs (Rizi et al, 2003;Hong et al, 2005) while human in vivo 3 He MRI to CT image registration has been reported as part of a study on the feasibility of lung cancer treatment planning with 3 He MRI (Ireland et al, 2007a). Furthermore, the importance of the image acquisition procedures on the resultant image registration of 3 He MRI to CT has been demonstrated (Ireland et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Image registration of hyperpolarized gas MRI has previously been published in the context of perfusion MRI using controlled gas administration in pigs (Rizi et al, 2003;Hong et al, 2005) while human in vivo 3 He MRI to CT image registration has been reported as part of a study on the feasibility of lung cancer treatment planning with 3 He MRI (Ireland et al, 2007a). Furthermore, the importance of the image acquisition procedures on the resultant image registration of 3 He MRI to CT has been demonstrated (Ireland et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…At present, pulmonary blood flow is evaluated by lung perfusion scintigraphy, perfusion computed tomography (CT) [13][14][15][16], and magnetic resonance imaging (MRI) [17][18][19][20][21]. Although these examinations are useful for assessing the pulmonary blood flow pattern, they are not simple procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Its unsurpassed soft-tissue contrast for example has been used for ventilation-perfusion imaging [1][2][3][4][5][6][7][8][9]. MRI of the lung may also be used to detect and measure broadening of tumors invading the chest wall or mediastinal structures [10].…”
Section: Introductionmentioning
confidence: 99%